Cadogan & Lee’s (2010) Suggestion for Measuring Endogenous Formative Variables: An Empirical Example. - Suoniemi Samppa; Terho Harri; Olkkonen Rami (Turkey, 2025)
In recent methodological articles related to structural equation modeling, the question of how to measure endogenous formative variables has been raised as an urgent, unresolved issue. This paper presents an empirical example from the CRM system development context to test Cadogan & Lee (2010)’s conceptual suggestion, which addresses this technical dilemma. PLS path modeling is used to demonstrate the feasibility of measuring antecedent relationships at the formative dimension level, not the formative construct level. The results indicate that Cadogan & Lee’s (2010) suggestion is a useful approach to assessing structural equation models with endogenous formative constructs.
Proceedings of the 42nd annual European Marketing Academy conference